An F-norm on sequences spaces - Idris, Mochammad (Hilbert Journal of Mathematical Analysis, 2024)
On sequences spaces, we can choose a Young function that plays a role in determining their norm structure. In this article, we modify the Young function by replacing its convexity property with concavity to define the F-norm in these spaces. Furthermore, we explore the properties of the modified Young function. Additionally, we investigate the completeness of the space, allowing it to be classified as an F-space (Frechet space).